ISBAT NIKAH DALAM PERSPEKTIF KOMPILASI HUKUM ISLAM HUBUNGANNYA DENGAN KEWENANGAN PERADILAN AGAMA - Zaidah, Yusna (Syariah: Jurnal Hukum dan Pemikiran, 2013)
As one of the executors of judicial power in the courts in the Indonesian Religious Court is given the jurisdiction over civil causes of Islam, one of which is in the field of marriage. As an Islamic court, the substantive law that is used Islamic law, then it is often defined as fiqh, which are certainly vulnerable difference. To bridge differences and to create legal certainty, as well as to realize the Islamic law, then Compilation of Islamic Law (KHI) was born which positively main themes of Islamic law in Indonesia and as one of the law applied in the Religious Court. Especially with regard to matters of marriage is a matter of legalization of marriage in Islamic Law Compilation qualified as a remedy called "the isbat of marriage". Of a jurisdictional basis isbat marriage cases as authority Religious Court Compilation of Islamic Law is one of the sources of law which raised more detailed reasons filing. Although the Compilation of Islamic Law is not included in the hierarchy of legislation. However, in order to fill the legal vacuum, the provisions governing the confirmation of marriage is considered as a policy that is needed by the religious court as justice of Islam in Indonesia.